Kualitas dan Daya Simpan Ikan Kakap Merah dengan Daun Beluntas (Pluchea indica L.) sebagai Pengawet Alami - Andriyana, Adi Dhian Putri Dwi, Dra. Titik Suryani, M.Sc (2017)
Red Snapper is one type of sea water fish that has economic value is high enough and much in demand because the meat is tasty and the protein content is high enough. Nutritional content of red snapper per 100 gram of water 77 g, calories 92 g, 29 g protein, 0.7 g fat, calcium 20 mg, phosphorus 200 mg, and iron 1 mg. Red snapper easily damaged because the protein and high water content so that the media grow microorganisms. The active compounds of beluntas leaf are flavonoids, essential oils, phenolics, tannins and alkaloids can be utilized as natural preservatives that can inhibit microbial activity. The purpose of this study was to quality and storage capacity of red snapper. The research method using Completely Randomized Design (RAL) with two factors, the first was the weight of beluntas leaf that were (B1 = 40 g, B2 = 50 g, B3 = 60 g), the second was soaking time (M1 = 30', M2 = 60') and control was K + (0.12 gram of Sodium benzoate) and K- (used aquades). The results showed the best quality of red snapper on B3M2 treatment (60 g beluntas leaf + 100 ml aquades and 60' soaking time) with the numbering bacterial colony 2,17 x 106 cfu / g, water content 43,4% and pH 6,1 with red appearance, fresh, solid texture and chewy, brownish gill color and stand out eye balls, and 18 hours of storage and can still be consumed.